Fish-powered progress: The unsung hero of food systems transformation - Gichohi, Wanjiku; Wismen, Bendula; Thilsted, Shakuntala (CGIAR Nutrition Impact Platform, 2025)
WorldFish’s research and development programs have piloted and scaled fresh fish, dried fish and fish powder to bridge production systems and consumer wellbeing. This video showcases the various activities across the Pacific, Asia and Africa implemented to deliver essential nourishment while benefiting food systems. Dive into the inspiring story of fish-powered progress!